Defending against speculative attacks - Tijmen R. Daniëls; Henk Jager; Franc Klaassen (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
While virtually all currency crisismodels recognise that the fate of a currency peg depends on how tenaciously policy makers defend it, they seldom model how this is done. We incorporate themechanics of speculation and the interest rate defence against it in the model ofMorris and Shin (American Economic Review 88, 1998). Our model captures that the interest rate defence reduces speculators' profits and thus postpones the crisis. It predicts that well before the fall of a currency interest rates are increased to offset the buildup of exchange market pressure, and this then unravels in a sharp depreciation. This pattern is at odds with predictions of standard models, but we show that it fits well with reality.
Keywords: E58; F31; F33; G15; 330; Exchange market pressure; currency crisis; interest rate defence; global game; Devisenspekulation; Währungskrise; Wechselkurspolitik; Devisenmarkt; Spieltheorie; Theorie